Fetal cerebellum intrauterine growth curve determined by ultrasound - Pacheco Romero, José (2015)
OBJETIVE: To determine the growth curve of the fetal cerebellum in uncomplicated pregnancies. DESIGN: Prospective, cross-sectional study. MATERIALS AND METHODS: the transverse cerebellar diameter was determined in 1050 fetuses of mothers without pregnancy complications cde. The study was conducted at the Department of Obstetrics ultrasound Edgardo Rebagliati Martins National Hospital, EsSalud, Lima, Peru. For statistical analysis, s used the Epi-Info 6.0 program. RESULTS: A growth curve gradual and progressive fetal cerebellum to 40 weeks was obtained, when it seems slow their growth. Erta growth curve seemed more remarkable than biparietal growth curves, abdominal circumference and femur in the same population. Compared with a foreign population of cerebellar growth curve he showed some differences after 28 weeks of gestation. CONCLUSIONS: The growth curve of intrauterine fetal cerebellum (R = 0.95) is correlated with gestational age. Suggested inclusion in routine ultrasound during pregnancy report